Defamiliarized family the “Anak ng OFWs’” emergent narratives on mediated communication and parent-child relationships - Pinzon, Mary Jannette L. (Plaridel, 2021)
Access online through this link: https://www.plarideljournal.org/article/defamiliarized-family-the-anak-ng-ofws-emergent-narratives-on-mediated-communication-and-parent-child-relationships